RISK MANAGEMENT EDUCATION FOR ADOLESCENTS: RECOGNIZING AND AVOIDING THE DANGERS OF PROMISCUITY - Sabri, Sabri; Suyono, Suyono; Ismail, Riswandhi; Sarmini, Sarmini; Edward, Febri (International Journal of Engagement and Empowerment (IJE2), 2025)
Risk Management is all actions to minimize anything that is not desired. So, things are done to prevent these negative impacts. In relation to this, in adolescent education it is very important to include character values ​​in educational goals. One of them is about Adolescent Socialization. In this case, the PKM TEAM held a community service at SMP and SMK Ibnu Sina Kabil, Batam with the theme: Risk Management Education for Adolescents: Recognizing and Avoiding the Dangers of Free Association. This activity aims to teach students how to understand Education in recognizing and avoiding risks that may arise as a result of the dangers of free association. The problems that are currently rampant among adolescents related to Free Association require handling and the PKM TEAM contributes to providing Risk Management Education in this regard. The participants were around 200 students at SMP and SMK Ibnu Sina Kabil, Batam. Which was held for two days, namely November 20-21, 2024.